ANALISIS TINDAK TUTUR ILOKUSI FILM PENDEK â€œNANTI KITA CERITA TENTANG HARI INI THE SERIES EPS 01â€ PADA KANAL YOUTUBE TOYOTAINDONESIA - Ariyadi, Ade Dufadhol; HP, Mahatma Krishna; Yudi Utomo, Asep Purwo (Universitas Wijaya Kusuma Surabaya, 2021)
AbstractToday, films have become a means of communication and conveying ideas that are increasingly massive. However, the purpose of dialogue and communication in films is sometimes not understood by most ordinary people. Therefore, we analyzed the speech act (dialogue) of one of the short films entitled